Aerobic Glycolysis: Beyond Proliferation - Jones, William; Bianchi, Katiuscia (Frontiers in Immunology, 2015)
Aerobic glycolysis has been generally associated with cancer cell proliferation, but fascinating and novel data show that it is also coupled to a series of further cellular functions. In this Mini Review we will discuss some recent findings to illustrate newly defined roles for this process, in particular in non malignant cells, supporting the idea that metabolism can be considered as an integral part of cellular signalling. Consequently, metabolism should be regarded as a plastic and highly dynamic determinant of a wide range of cellular specific functions.